Quality of life of patients after anterior cruciate ligament reconstruction using LARS synthetic graft and autogenous ST/GR graft - Płocki, Jędrzej; Kotela, Ireneusz; Bejer, Agnieszka; Pikuła, Dominik; Probachta, Mirosław; Kotela, Andrzej (Medical Studies/Studia Medyczne, 2017)
Introduction : Injury to the anterior cruciate ligament (ACL) causes disorders in the functional capabilities of the limb, both in daily life and during attempts to return to full physical activity, and in a later period it contributes to the development of degenerative disease. Aim of the research : Determination of the level of quality of life in patients after ACL reconstruction using the LARS synthetic ligament or autogenous ST/GR graft 4 years after surgery. Material and methods : Into the study were qualified 96 patients who had undergone reconstruction due to injury to the anterior cruciate ligament. The patients were divided into two groups according to the type of material used for reconstruction. The study group included 44 (45.8%) patients who were operated on using the LARS synthetic ligament. The control group comprised 52 (54.2%) patients who were implanted with an autogenous graft from semitendinous or gracilis muscle. The study was conducted using the SF36v2 questionnaire for the assessment of quality of life. Results: The patients expressed the most negative evaluations of quality of life in the domain of General Health (GH) (x– = 62.5 scores) and Mental Health (MH) (x– = 70.4 scores), whereas most positive evaluations concerned the domain related with role limitations – caused both by physical health (Role Pysical – RP) and emotional problems (Role Emotional – RE) (x– > 95 scores). No statistically significant differences in the level of the quality of life were observed in the two selected groups; however, the evaluation of the quality of life in the area of social functioning and psychological health were slightly higher in the group of patients who had undergone surgery using the LARS method. Conclusions : The quality of life of patients within the period of 4 years after ACL reconstruction procedure using the LARS method and autogenous graft was on a similar, high level.